The role of the vagus nerve in the generation of cardiorespiratory interactions in a neotropical fish, the pacu, Piaractus mesopotamicus - Costa Leite, Cleo Alcantara; Taylor, E. W.; Guerra, C. D. R.; Florindo, L. H. [UNESP]; Belao, T.; Rantin, F. T. (Springer, 2009)
The role of the vagus nerve in determining heart rate (f (H)) and cardiorespiratory interactions was investigated in a neotropical fish, Piaractus mesopotamicus. During progressive hypoxia f (H) initially increased, establishing a 1:1 ratio with ventilation rate (f (R)). Subsequently there was a hypoxic bradycardia. Injection of atropine abolished a normoxic inhibitory tonus on the heart and the f (H) adjustments during progressive hypoxia, confirming that they are imposed by efferent parasympathetic inputs via the vagus nerve. Efferent activity recorded from the cardiac vagus in lightly anesthetized normoxic fish included occasional bursts of activity related to spontaneous changes in ventilation amplitude, which increased the cardiac interval. Restricting the flow of aerated water irrigating the gills resulted in increased respiratory effort and bursts of respiration-related activity in the cardiac vagus that seemed to cause f (H) to couple with f (R). Cell bodies of cardiac vagal pre-ganglionic neurons were located in two distinct groups within the dorsal vagal motor column having an overlapping distribution with respiratory motor-neurons. A small proportion of cardiac vagal pre-ganglionic neurons (2%) was in scattered positions in the ventrolateral medulla. This division of cardiac vagal pre-ganglionic neurons into distinct motor groups may relate to their functional roles in determining cardiorespiratory interactions.
Keywords: Cardiorespiratory interactions; Piaractus mesopotamicus; Vagus nerve; Heart rate; Cardiac vagal pre-ganglionic neurons